2013
DOI: 10.1093/humupd/dmt045
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of intrauterine adhesions after miscarriage: prevalence, risk factors and long-term reproductive outcome

Abstract: IUAs are frequently encountered, in one in five women after miscarriage. In more than half of these, the severity and extent of the adhesions was mild, with unknown clinical relevance. Recurrent miscarriages and D&C procedures were identified as risk factors for adhesion formation. Congenital and acquired intrauterine abnormalities such as polyps or fibroids were frequently identified. There were no studies reporting on the link between IUAs and long-term reproductive outcome after miscarriage, while similar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
227
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(241 citation statements)
references
References 91 publications
7
227
0
7
Order By: Relevance
“…In women undergoing secondary procedures to remove placental remnants after delivery or repeat curettage, IUAs are found in 40 % [10]. The results of a recent systematic review of IUA after miscarriage are in line with previous findings [11]. In a cohort study, hysteroscopic cold loop resection of placental remnants showed a lower rate (4.2 %) of IUAs at routine second-look hysteroscopy as compared with ultrasound-guided curettage using a metal curette (30.8 %) [12].…”
Section: Clinical Significance Of Postoperative Adhesions Hysteroscopysupporting
confidence: 78%
See 1 more Smart Citation
“…In women undergoing secondary procedures to remove placental remnants after delivery or repeat curettage, IUAs are found in 40 % [10]. The results of a recent systematic review of IUA after miscarriage are in line with previous findings [11]. In a cohort study, hysteroscopic cold loop resection of placental remnants showed a lower rate (4.2 %) of IUAs at routine second-look hysteroscopy as compared with ultrasound-guided curettage using a metal curette (30.8 %) [12].…”
Section: Clinical Significance Of Postoperative Adhesions Hysteroscopysupporting
confidence: 78%
“…Routine second-look hysteroscopy should be performed after surgical interventions for removal of placental remnants to further assess the risk of IUA formation [14]. Hysteroscopic treatment, allowing for selective removal of placental remnants and thus minimizing the risk of unnecessary trauma to the uterine cavity, may be the preferred surgical treatment [11].…”
Section: Clinical Significance Of Postoperative Adhesions Hysteroscopymentioning
confidence: 99%
“…1 IUA increases the risk of menstrual abnormalities, secondary infertility, recurrent miscarriage, and pregnancy complications. 2 Common treatments include hysteroscopic adhesiolysis and administration of hormonal drugs to promote the regeneration of the endometrial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15 -20% of all clinically recognized pregnancies will end in a miscarriage [4,9,10]. However, prospective cohort studies using sensitive and specific daily urinary hCG assays in women trying to conceive have demonstrated that only around one-third of conceptions progress to a live birth.…”
Section: Epidemiologymentioning
confidence: 99%